Examining student burnout causes among English as a foreign language students: focus on school climate and student growth mindset - Liu, Xiaoling (Frontiers in Psychology, 2023)
Introduction The aim of this study was to investigate the relationship between student burnout and two key factors - perceived school climate and growth mindset - in the context of English as a foreign language (EFL) learning among Chinese students. Methods A sample of 412 intermediate English language learners from China participated in an online survey and completed valid measures of the three constructs. Confirmatory factor analysis (CFA) was used to establish the validity of the scales used to measure the three latent variables. Structural equation modeling (SEM) was then used to test the proposed model. Results The results of SEM showed that both perceived school climate and growth mindset had a significant positive impact on EFL student burnout, with perceived school climate having a stronger effect compared to growth mindset. Discussion The findings suggest that promoting a positive school climate and fostering a student growth mindset can help reduce student burnout in EFL settings.